Examining the relationship between basic psychological needs and athlete identity during the COVID-19 pandemic - Parker, P. C.; Beeby, A. M.; Daniels, L. M. (Frontiers in Psychology, 2022)
Objectives: During COVID-19 athletes have had games canceled, seasons postponed, and social supports lost. These changes negatively impact their motivation, and potentially identity, as athletes. We draw on self-determination theory to examine motivation in sport and its relationship with athlete identity during COVID-19.